The Influence of Current Ratio, DER and Total Asset Turnover on Profit Growth in Manufacturing Companies in the Goods and Consumer Goods Industry Sub-Sector Listed on the Indonesian Stock Exchange 2019 -2022 - Dinatonia Jovery Matruty; Anna Valensia Christianty de Fretes; Sari Fatimah (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study aims to examine the Current Ratio, Debt To Equity Ratio, and Total Asset Turnover on profit growth in manufacturing companies in the goods and consumption industry sector listed on the Indonesia stock exchange. The population in this study are manufacturing companies in the goods and consumer goods industry sub-sector listed on the Indonesia stock exchange for the period 2029-2022. The sample in this study is the Financial Statements of Manufacturing Companies in the 2019-2022 goods and consumption industry sub-sector which were taken using purposive sampling method, so that 15 companies were obtained as samples. And using the multiple linear analysis method, classical assumption test, t test (partial test), and the coefficient of determination with the SPSS (Statistical Product and Service Solution) v16 software. Based on the results of the research, it can be concluded that partially the Current Ratio has a positive and significant effect on profit growth, while the Debt to Equity Ratio has a positive and significant effect on profit growth as well as the Total Asset turnover has a positive and significant effect on profit growth in manufacturing companies in the goods and consumer goods industry sub-sector listed on the Indonesian stock exchange for the 2019-2022 period.